Associations between Ethnicity and Referrals, Access and Engagement in a UK Adult Burns Clinical Psychology Service - Laura Shepherd; Ishani Hari; Lauren Bamford (MDPI AG, 2023)
Ethnic inequalities exist across healthcare, including access to and experiences and outcomes of mental health services. Access to and engagement with burns clinical psychology services is essential for all patients. This study aimed to explore the ethnic diversity of adults referred to a burns clinical psychology service compared to those admitted to the burns service. It also aimed to investigate associations between ethnicity and indicators of access and engagement (receiving, declining or not attending psychological assessments, receiving psychological therapy and the number of therapy sessions completed). Routinely collected data over eight years were analysed. Analysis revealed an association between ethnicity and referral to the burns clinical psychology service. Patients from White British and Other ethnic backgrounds were less likely to be referred, whereas patients from Black and Asian ethnic groups were more likely to be referred. There were no statistically significant associations between ethnicity and receiving, declining or not attending psychological assessments or receiving psychological therapy. Furthermore, there was no statistically significant difference in the number of psychological therapy sessions received between the ethnic groups. Therefore, patients from ethnic minority groups did not appear to have significant difficulties engaging with the service but further research is recommended.